2021
DOI: 10.1007/s42399-021-00873-9
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Infections of Oral Cavity: Diagnosis, Management, and Association with COVID-19

Abstract: The frequency of fungal infections is increasing due to immunodeficiency viruses and immunosuppressive drugs. The most common fungal infection of the oral cavity is candidiasis. The existence of Candida can be a part of normal commensal; hence, the isolation of Candida in the absence of clinical symptoms should exclude candidiasis. The pathogenicity of Candida is witnessed as opportunistic when immune status is compromised. Oral fungal infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 85 publications
(93 reference statements)
0
45
0
Order By: Relevance
“…Syphilis, tuberculosis, leprosy, scarlet fever, and gonorrhea are some of the causes of nonodontogenic oral infections [ 7 ]. Most fungal infections are opportunistic in nature; oral candidiasis, caused by Candida , is the most commonly encountered oral fungal infection in clinical practice [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Syphilis, tuberculosis, leprosy, scarlet fever, and gonorrhea are some of the causes of nonodontogenic oral infections [ 7 ]. Most fungal infections are opportunistic in nature; oral candidiasis, caused by Candida , is the most commonly encountered oral fungal infection in clinical practice [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…12,13,[18][19][20]23,28,30,42 Diagnosis of invasive aspergillosis, mucormycosis, and other opportunistic fungal infections occurs frequently during post-mortem examinations. 17,22,39,43,44 A recent case series of 18 patients with COVID-19 in India found that 16 developed mucormycosis, six of them with a fatal outcome (>37%). 28 Another series of 10 patients in India identified 10 patients with CAM, suggesting that this condition is more common than expected.…”
mentioning
confidence: 99%
“…Hence, healthcare settings may also find challenging to treat the mucormycosis and serves as burden to hospitals and society. Thus, mucormycosis is certainly an important co-morbid condition to be listed as associated oral fungal infections in COVID-19 infection [ 2 ].…”
mentioning
confidence: 99%